Tatárszentgyörgytől Tatárszentgyörgyig . From Tatárszentgyörgy to Tatárszentgyörgy - Daróczi, Joka (MTV - Hungarian Television, 2009)
Verzio FF Submission A film about the rise of the far right movement in Hungary in 2009, and about the Hungarian Guard, a paramilitary organization that defines itself as group aiming to protect Hungarian traditions and culture. Though openly racist and anti-Semitic they enjoy the support of hundreds of thousands of Hungarians. This film follows the Guard’s activities in recent years.